Robert Browning - Wood, S. author. aut Link
XVII, 232 p.
Keywords: Browning both denied and affirmed the value of biography for an understanding of literature. This book narrates the development of his controversial creative life through responses to his work by five key nineteenth-century figures: John Stuart Mill, William Charles Macready, Thomas Carlyle, John Ruskin and Matthew Arnold. It also relates Browning's sense of literary vocation to Victorian publishing. Browning emerges as a writer vividly engaged with contemporary assumptions, yet deeply aware of the unaccountability of writing.